The Genus Tegonotus Nalepa (Acariformes: Eriophyidae: Phyllocoptinae): Description of a New Species and Key to Valid Species - Eid Muhammad Khan; Jawwad Hassan Mirza; Muhammad Kamran; Fahad Jaber Alatawi (Diversity, 2025)
The genus Tegonotus Nalepa (Acariformes: Eriophyidae: Phyllocoptinae) is recorded for the first time from Saudi Arabia with the description of a new species, T. saudiensis sp. nov., collected from the inner fronds of Phoenix dactylifera L. (Arecaceae), described and illustrated based on females. The individuals of the new species were vagrant on the abaxial leaf surface, causing no apparent damage to the host plant. The taxonomic status of the genus and its species was thoroughly assessed through the literature-based analysis of morphological characters. Consequently, the diagnosis of the genus Tegonotus is updated, and a key to 47 valid species is provided. Eight Tegonotus species are suggested to be transferred to three different genera within the tribe. A brief discussion on the taxonomic status of these species is provided. The position of scapular tubercles and setae (sc), and shape of the dorsal pedipalp genu seta (d), were found to be significant for the generic designation.